Clinical phenotype of a Kallmann syndrome patient with IL17RD and CPEB4 variants - Zhang, Jianmei; Yang, Suhong; Zhang, Yan; Liu, Fei; Hao, Lili; Han, Lianshu (Frontiers in Endocrinology, 2024)
Background: This study aimed to characterise the clinical phenotype and genetic variations in patients with Kallmann syndrome (KS).Methods: This study involved the collection and analysis of clinical data from an individual with sporadic KS. Following this, peripheral blood samples were obtained from the patient and his parents. Genomic deoxyribonucleic acid was extracted and subjected to whole-exome sequencing and genomic copy number variation (CNV) detection. Finally, Sanger sequencing was performed to validate the suspected pathogenic variants.Results: Whole-exome sequencing confirmed that the child carried both the IL17RD variant (c.2101G>A, p.Gly701Ser) inherited from the mother and the new CPEB4 variant (c.1414C>T, p.Arg472*) . No pathogenic CNVs were identified in CNV testing.Bioinformatics analysis shows that the IL17RD protein undergoing Gly701Ser mutation and is speculated to be phosphorylated and modified, thereby disrupting fibroblast growth factor signaling. This study also suggested that the CPEB4 might play a crucial role in the key signalling process affecting olfactory bulb morphogenesis. Overall, the findings of this study broaden the gene expression profile of KS-related pathogenic genes. This offers a new avenue for exploring the pathogenic mechanism of KS and provides valuable insights for precise clinical diagnosis and treatment strategies for this condition.